The Relationship between Comparative Adult Basic Education Approaches and Poverty Alleviation in Selected Tay, H'mong, Dao and Black Thai Communities in Vietnam. - Colman Patrick Ross; Carmel O' Sullivan (Comparative Education Society of Iran ( CESIR), 2018)
This paper examines two approaches to Adult Basic Education and their influence on accessing poverty alleviation resources in selected ethnic minority communities in Vietnam. In a multiple case study that relied heavily on structured and semi-structured interviews, investigations focused on the curricula, methodology, teacher / facilitator training, use of local languages, link to poverty alleviation and post-course use of literacy and literate environments by participants in each of the three selected case study communities. Although there are numerous models and methods for implementing ABE programmes, this paper focuses on Reflect and the Government of Vietnam's Adult Literacy Programme implemented by local education authorities. Reflect an approach developed by ActionAidis based on the theory of conscientisation, pioneered by Paulo Freire. Adult learners explore development challenges and these become the basis to be taught literacy and numeracy skills. Findings concentrate on: How do differences in ABE / literacy approaches impact on how specific ethnic minorities access specific poverty alleviation resources in Vietnam?